An engaging consult with DeepSeek about acute abdomen - Kannan, Sanjaikrishna Pakkirisamy (International Surgery Journal, 2025)
DeepSeek is a large language model (LLM) developed by Hangzhou DeepSeek artificial intelligence basic technology research Co., Ltd., a Chinese artificial intelligence company based in Hangzhou, China. Ever since its launch in July 2023, DeepSeek has released several revised and updated versions, with the latest being DeepSeek-R1 which is free for use unlike other advanced LLM counterparts.